2020
DOI: 10.36660/abc.20200372
|View full text |Cite
|
Sign up to set email alerts
|

Biomarcadores de Lesão Miocárdica e Complicações Cardíacas Associadas à Mortalidade em Pacientes com COVID-19

Abstract: Background: SARS-CoV-2 is an emerging RNA virus associated with a severe acute respiratory disease known as COVID-19. Although COVID-19 is predominantly a pulmonary disease, some patients have severe cardiovascular damage. We performed a quantitative evidence synthesis of clinical data, myocardial injury biomarkers, and cardiac complications associated with in-hospital death in patients with COVID-19. Methods: We searched the databases PubMed, Embase, and Google Scholar to identify studies comparing clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Furthermore, the study revealed that concomitant treatment with corticosteroids may have resulted in a better response with anakinra treatment. 71 These findings illustrate the value of using medications based on biomarkers such as the anti-cytokine tocilizumab and anakinra to improve outcomes for patients with COVID-19. Clinicians can measure the levels of cytokines such as IL-6 to identify the early stages of the cytokine storm and administer anti-cytokine medications to improve patient outcomes.…”
Section: Role Of Biomarkers In Treatmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, the study revealed that concomitant treatment with corticosteroids may have resulted in a better response with anakinra treatment. 71 These findings illustrate the value of using medications based on biomarkers such as the anti-cytokine tocilizumab and anakinra to improve outcomes for patients with COVID-19. Clinicians can measure the levels of cytokines such as IL-6 to identify the early stages of the cytokine storm and administer anti-cytokine medications to improve patient outcomes.…”
Section: Role Of Biomarkers In Treatmentmentioning
confidence: 87%
“…Cytokine inhibitors have decreased mortality in patients with severe COVID-19, highlighting their role in preventing COVID-19 deaths. 71 An observational study was conducted to confirm the optimal timing of IL-6 receptor inhibitor (IL-6ri) administration for 255 COVID-19 patients. During the IL-6ri administration, patients were divided into 2 groups; the stage IIB group required less than 45% of inspired oxygen (FiO 2 ), and the stage III group required more than 45% of FiO 2 .…”
Section: Role Of Biomarkers In Treatmentmentioning
confidence: 99%
“…Considerando a alta taxa de morbimortalidade da COVID-19, os idosos, a partir de 60 anos, foram considerados o maior grupo de risco. A fragilidade do sistema imunológico e aumento de comorbidades nessa população, os tornam mais susceptíveis às formas graves, em caso de contato com a doença (Martins et al, 2020). Autores afirmam que durante o período pandêmico elevou-se o número da população sedentária, devido às recomendações para que a população aderisse à s medidas de isolamento domiciliar.…”
Section: Discussionunclassified
“…There is growing evidence of an association between myocardial injury and an increased risk of death in patients with COVID-19. Several studies involving patients with confirmed COVID-19 have implied the elevation of serum hTnI not only with mortality, 4,[12][13][14][15][16][17][18][19] but also criticality. 8,14,16 Although some investigators 4,14,16,18 have found an association between inflammatory biomarkers with poor prognosis, in the present study, only higher levels of hTnI were independently associated with mortality (table 3).…”
Section: Discussionmentioning
confidence: 99%